Pengaruh Bimbingan Kelompok Dengan Teknik Diskusi Terhadap Self Confidence Pada Anak Yang Berhadapan Dengan Hukum - Miftahuddin, Miftahuddin; Annisa, Laura (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The problem of children in conflict with the law (ABH) is a social issue that demands attention. Children involved in the justice system often experience complex emotional, psychological, and social challenges. Children in conflict with the law often experience significant emotional and psychological stress. They face stigma from society, which can worsen their mental condition and hinder their social development. This pressure can reduce their self-confidence, which negatively impacts their ability to face challenges and build healthy social relationships. At the Abiseka Pekanbaru Center, these children need special support to develop their self-confidence again. Children as the younger generation are the successors in the process of growing towards adulthood, sometimes they do not comply with what parents expect because in the development of increasingly advanced times, children's thinking patterns and character are decreasing, which makes children able to commit criminal acts nowadays, this is due to children's lifestyles. Now it's bad because you always put your self-esteem first and follow the wrong social style. This research aims to determine the effect of group guidance on self-confidence in children in conflict with the law (ABH) at the Abiseka Center in Pekanbaru. This research uses quantitative methods. With a total population of 29 children and samples were taken using total sampling techniques so that 29 children were obtained. Data collection techniques by distributing online questionnaires and documentation. In this study, the variable (X) is group guidance, while the variable (Y) is self-confidence. After processing the data, a correlation result was found of 0.622, which means that this research has a strong relationship between variable (X) and variable (Y). then an R square value of 0.387 was found, which means that the influence of Group Guidance (X) on Self-Confidence (Y) is 38.7%.